EP 56. Optogenetic control of the locus coeruleus in mice: Behavioral and electrophysiological data. Issue 9 (September 2016) - Janitzky, K.; Lippert, M.; Tegtmeier, J.; Heinze, H.-J.; Ohl, F.W.
Abstract : The locus coeruleus (LC) is the sole source of noradrenergic projections to the cortex and to better understand its essential role for attention-dependent cognitive processes, we first expressed the halorhodopsin eNpHR3.0 to reversibly silence LC activity in naive male B6.Cg-Tg(Th-cre)1Tmd/J hemizygous mice (Th-cre mice) that express Cre-recombinase under the control of the tyrosine hydroxylase (TH) promoter. Unilateral optogenetic silencing of the LC during the performance of an attentional set-shifting task (ASST) selectively impaired learning of those parts of the ASST that most strongly rely on cognitive flexibility. In particular, extra-dimensional set-shifting (EDS) and reversal learning was impaired. However, those parts of the task that are less dependent on cognitive flexibility, i.e. compound discrimination (CD) and the intra-dimensional shifts (IDS), as well as attentional set formation were unaffected by LC silencing. Therefore, our results suggest a modulatory influence of the LC on cognitive flexibility, mediated by different frontal networks. Subsequently, we used AAV8-Ef1a-DIO-Chronos-eYFP to stimulate LC activity in Th-cre mice and performed electrophysiological recordings during optogenetic stimulation by using an optetrode. Laser pulses of different intensities (0.5, 1, 2, 5, and 10 mW) and different pulse durations (5, 10, 20, 50, 100, 200, and 500 ms) were tested. Results showed that pulses at 5 mW of 5 ms pulse duration are optimal and that those laser pulses are able to induce bursts of 20 Hz discharges and sustained 10 Hz discharges of LC neurons.